1997
DOI: 10.1038/bjc.1997.515
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged survival by 'early' salvage treatment of breast cancer patients: a retrospective 6-year study

Abstract: Summary Between 1977 and1993, 384 breast cancer patients were followed up post-operatively every 4 or 6 months with a serum tumour marker panel (CEA-TPA-CA1 5-3) and the usual imaging techniques. Twenty-eight patients were treated 13.5±10 months (mean±s.d.) before the clinical and/or radiological occurrence of distant metastases that were suspected because of an increase in the tumour markers (patients treated 'early'). Their outcome was compared with that of 22 similar patients who were treated only after a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 16 publications
0
24
0
3
Order By: Relevance
“…We found that in some untreated patients CEA, TPA and CA15.3 anticipated by 2.7-5.1 months the clinical-instrumental signs of distant metastases [28,37,47] according to other authors' data [13]. Table 5 shows the various kinds of tumor marker Table 5.…”
Section: Reliability Of Tumor Markers For Early Detection Of Distant mentioning
confidence: 91%
See 2 more Smart Citations
“…We found that in some untreated patients CEA, TPA and CA15.3 anticipated by 2.7-5.1 months the clinical-instrumental signs of distant metastases [28,37,47] according to other authors' data [13]. Table 5 shows the various kinds of tumor marker Table 5.…”
Section: Reliability Of Tumor Markers For Early Detection Of Distant mentioning
confidence: 91%
“…Twenty-eight patients treated before the clinical and/or radiological detection of distant metastases because of an increase in tumor markers suggesting relapse (patients treated 'early') were compared with 22 patients similar in all major prognostic factors who were treated only after a definite radiological diagnosis was obtained (patients treated 'not early'). For patients treated 'early' the survival curves up to 30 months after salvage treatment and up to 72 months after mastectomy showed a superior survival to that of patients treated later (p = 0.04 in both instances) [47]. Further work is in progress.…”
Section: Therapy Following Early Detection Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, many centres world-wide perform serial CA15-3 measurements in the routine followup of these patients as for some women it provides the earliest evidence of recurrent disease, for which mul-tiple forms of treatment are available, and intuitively it might be hoped that the earlier treatment is initiated, the better the outcome. Firm evidence demonstrating that early initiation of treatment based on this lead-time improves patient outcome or quality of life is lacking although a small number of papers do suggest a benefit in outcome adopting this approach [20][21][22].…”
Section: Breast Cancermentioning
confidence: 99%
“…After an average follow-up of 11 months, 7 out of 29 patients (24%) in the control group had relapsed, whereas none of the 23 patients who had received treatment developed a recurrence (p= 0.012). Nicolini et al (Nicolini et al, 1997; compared the outcomes in 36 asymptomatic patients who received salvage treatment based on tumour marker increases (CA 15-3, CEA, or TPA) with 32 patients who were given treatment only after radiologic confirmation of metastasis. Survival from both the time of mastectomy and salvage treatment was significantly improved in the group with tumour marker-guided treatment than in those treated conservatively.…”
Section: Tumour Markers and Surveillance After Primary Treatmentmentioning
confidence: 99%